Diferentes atividades didáticas sobre animais peçonhentos em uma escola rural da região central do RS - Guerra, Leonan (2016)
The accidents caused by poisonous animals are a serious public health problem, especially in tropical countries because of its wide distribution and its ability to promote clinical conditions that may progress to the death. In this sense deepen the knowledge about poisonous animals and disseminate information through the use of a teaching strategy called Didactic Pluralism consisting in the use of various methodological resources to meet all students and not a portion of them may be the way to education on venomous animals. Therefore this research has as main objective investigate how the educational pluralism can be worked at the classroom, with a proposal to assist students in learning about poisonous animals and accident prevention. The research was developed on Elementary School Almiro Beltrame, located in the Rural Area of the Boca do Monte district in the city of Santa Maria, at the central region of Rio Grande do Sul - Brazil, from October 2014 to July 2015. The instruments of data collection were: conversation with audio recording, video, script and practice class logbook developed by the researcher. By the analyzed qualitatively of the activities that make up this research and the results showed that the teaching of venomous animals was favored by educational pluralism. Thus, the students in addition to the personal care, may become multipliers of information for families and others close to them, leading to a likely decline in the number of accidents by preventing and understanding of the ecological importance of venomous animals. Therefore we hope that this research will contribute to the area of science education and to the inclusion of these teaching methods in the teaching practice.